Neutrophils expressing lysyl oxidase‐like 4 protein are present in colorectal cancer liver metastases resistant to anti‐angiogenic therapy. Issue 2 (18th May 2020) - Palmieri, Vincent; Lazaris, Anthoula; Mayer, Thomas Z; Petrillo, Stephanie K; Alamri, Hussam; Rada, Miran; Jarrouj, George; Park, Woong‐Yang; Gao, Zu‐hua; McDonald, Patrick P; Metrakos, Peter
Abstract: Colorectal cancer liver metastases (CRCLM) that present with a replacement histopathological growth pattern (HGP) are resistant to neoadjuvant anti‐angiogenic therapy. Surrogate biomarkers are not available to preoperatively identify patients with these tumors. Here we identify differentially expressed genes between CRCLM with a replacement HGP and those with a desmoplastic HGP using RNA sequencing. We demonstrate that LOXL4 is transcriptionally upregulated in replacement HGP CRCLM compared with desmoplastic HGP CRCLM and the adjacent normal liver. Interestingly, lysyl oxidase‐like 4 (LOXL4) protein was expressed by neutrophils present in the tumor microenvironment in replacement HGP CRCLM. We further demonstrate that LOXL4 expression is higher in circulating neutrophils of cancer patients compared with healthy control patients and its expression can be induced by stimulation with lipopolysaccharide and TNF‐α. Our study is the first to show the expression of LOXL4 in neutrophils and reveals the potential for LOXL4‐expressing neutrophils to support the replacement HGP phenotype and to serve as a surrogate biomarker for this subtype of CRCLM. © 2020 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.